The Influence Of Technology On Language Acquisition and Development Of Grade IV Students - Nursalim Nursalim; Nadilla Resti Amanda; Wini Ihwana; Herdila Herdila (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The rapid development of information and communication technology has brought significant changes to education, particularly in language acquisition and development among elementary school students. Technologies such as interactive learning applications, educational videos, and e-learning platforms have become integral to the learning process at various educational levels. This study aims to identify and analyze the influence of technology use on language acquisition and development among Grade IV students at SD Islam Al-Azhar 54 Pekanbaru, and to provide strategic recommendations for effective technology integration in the language learning curriculum. This study employs a descriptive qualitative approach using the literature review method. Data were collected by examining 25 relevant references, including books, journal articles, and prior research obtained from various academic databases. Analysis was conducted thematically to identify patterns, findings, and research gaps. The findings show that 75% of students experienced increased motivation and engagement in language learning when using technology. The use of learning applications and audiovisual materials improved vocabulary mastery and grammatical comprehension. However, unequal access to devices and the risk of digital distraction remain key challenges that must be addressed through comprehensive school policies